Study of n-alkylamine Intercalated Layered Perovskite-Like Niobates HCa2Nb3O10 as Photocatalysts for Hydrogen Production From an Aqueous Solution of Methanol - Voytovich, Vladimir V.; Kurnosenko, Sergei A.; Silyukov, Oleg I.; Rodionov, Ivan A.; Minich, Iana A.; Zvereva, Irina A. (Frontiers in Chemistry, 2020)
A series of hybrid niobates HCa2Nb3O10×RNH2, containing intercalated into the interlayer space n-alkylamines (R = Me, Et, Pr, Bu, Hx, Oc), has been thoroughly studied concerning the photocatalytic splitting of the model aqueous solution of methanol for the first time. All the hybrid photocatalysts were synthesized by the conventional ceramic technique followed by protonation and intercalation of n-alkylamines. The products were characterized in details using XRD, Raman, IR, NMR and diffuse reflectance spectroscopy, TGA, CHN-analysis, SEM. Photocatalytic measurements were conducted according to a complex scheme taking into account changes in the photocatalyst concentration because of sedimentation, pH shifts and possible exfoliation of the samples into nanolayers. Special attention was also paid to the feasible improvement of the photocatalytic activity of the samples via their modification with Pt nanoparticles as a cocatalyst. In the series of amine derivatives, the highest rate of hydrogen generation was demonstrated by the Pt-loaded HCa2Nb3O10×BuNH2 reaching quantum efficiency of 13 % in the 220–340 nm range that was shown not to be due to a change in the bandgap energy during the amine intercalation. The amount of hydrogen evolved during the measurement significantly exceeded the amount of the interlayer amine indicating that hydrogen is generated rather from the methanol solution than from the intercalated organic component. Thus, modification of layered perovskite-like oxides by organic substances appears to be an effective strategy to manage their photocatalytic activity, which may be applied to other related photocatalytic materials.